1998
DOI: 10.1128/jb.180.3.547-555.1998
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus subtilis Cell Cycle as Studied by Fluorescence Microscopy: Constancy of Cell Length at Initiation of DNA Replication and Evidence for Active Nucleoid Partitioning

Abstract: Fluorescence microscopic methods have been used to characterize the cell cycle of Bacillus subtilis at four different growth rates. The data obtained have been used to derive models for cell cycle progression. Like that of Escherichia coli, the period required by B. subtilis for chromosome replication at 37°C was found to be fairly constant (although a little longer, at about 55 min), as was the cell mass at initiation of DNA replication. The cell cycle of B. subtilis differed from that ofE. coli in that chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
130
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 158 publications
(146 citation statements)
references
References 51 publications
16
130
0
Order By: Relevance
“…Many of the forces behind the presumed movements of DNA regions have not been found yet. A mitotic-like mechanism that actively segregates DNA has been suggested (for a review, see Glaser et al, 1997;Shapiro and Losick, 1997;Sharpe et al, 1998), and it has also been suggested that this mechanism exists alongside a mechanism for gradual movement of bulk DNA (Sharpe et al, 1998). We would like to add the possibility that DNA regions exhibit constrained diffusional motion, similar to that found in yeast and Drosophila (Marshall et al, 1997).…”
Section: Discussionmentioning
confidence: 93%
“…Many of the forces behind the presumed movements of DNA regions have not been found yet. A mitotic-like mechanism that actively segregates DNA has been suggested (for a review, see Glaser et al, 1997;Shapiro and Losick, 1997;Sharpe et al, 1998), and it has also been suggested that this mechanism exists alongside a mechanism for gradual movement of bulk DNA (Sharpe et al, 1998). We would like to add the possibility that DNA regions exhibit constrained diffusional motion, similar to that found in yeast and Drosophila (Marshall et al, 1997).…”
Section: Discussionmentioning
confidence: 93%
“…DNA manipulations and E. coli DH5α transformations were carried out using standard methods (Sambrook et al, 1989). Solid medium used for growing B. subtilis was nutrient agar (Oxoid), and liquid medium was either casein hydrolysate (CH) medium (Sterlini and Mandelstam, 1969) or S medium (Sharpe et al, 1998) supplemented with 1% (v/v) CH (S+), with antibiotics added as required. Chloramphenicol was used at 5 µg ml −1 , spectinomycin at 50 µg ml −1 , erythromycin at 1 µg ml −1 , kanamycin at 5 µg ml −1 and phleomycin at 0.2 µg ml −1 .…”
Section: General Methodsmentioning
confidence: 99%
“…For growth experiments, B. subtilis strains were grown at 37∞C in Difco Antibiotic Medium 3 (PAB) supplemented with 0.5 M sucrose, 20 mM maleic acid and 20 mM MgCl 2 (MSM) (Chang and Cohen, 1979) or with 0.5 M sucrose or 20 mM MgCl 2 alone and 0.5% xylose was added as necessary. For imaging of GFP fluorescence strains were grown at 30∞C in S medium (Sharpe et al, 1998) with 0.3% xylose or CH medium with 0.3% xylose and 20 mM MgCl 2 . For VAN-FL staining strains were grown at 30∞C PAB supplemented as before.…”
Section: Growth Conditionsmentioning
confidence: 99%